Traditional lands acquisition and compensation: The perceptions of the affected Aborigin in Malaysia - Alias, A.; Kamaruzzaman, S.N.; Daud, M.N. (Academic Journals, 2010)
This paper reports the issues of land acquisition and compensation related to the aboriginal people in Malaysia called Orang Asli. Unfortunately, the rights of the Orang Asli traditional lands are not clearly defined in the Malaysian legal system. This research adopts a questionnaire survey as the method of study, and descriptive analysis to present the results. The research revealed that laws of Malaysia are inadequate to protect the Orang Asli lands and their right to fair and just compensation. As practised now, in the absence of appropriate guidelines and regulations, the determination of compensation is based solely on the discretion of the various authorities. Furthermore, this research revealed that the compensation required by the Orang Asli should have both monetary and non-monetary components.